Antimicrobial Assessment of Resins from Calophyllum Antillanum and Calophyllum lnophyllum. - Cuesta Rubio, Osmany (2015)
The Calophyllum genus is well-known for its antimicrobial and cytotoxic activities, and therefore, we analyzed these biological activities for resins of Calophyllum antillanum and Calophyllum inophyllum growing in Cuba. C. antillanum resins sbowed a potent activity against Plasmodium falciparum (IC50 0.3 0.1 μg/mL), while its cytotoxicity against MRC-5 cells was much lower (IC50 2L6:t1.1 μglmL). In contrary, the resin of C. inophyllum sbowed an unspecific activity. The presence of apetalic acid, isoapetalic acid, calolongic acid, pinetoric acid pinetoric acid u, isocalolongic acid, pinetoric acid m, and isopinetoric acid m in c. antillanum resins was also confinned. These resuJts demonstrated for tbe first time tbe potential activity of C. antillanum resins against P.falciparum. Copyright© 2015 Jobo Wiley Sons, Ltd.